2015
DOI: 10.1051/0004-6361/201424397
|View full text |Cite
|
Sign up to set email alerts
|

Properties of solar energetic particle events inferred from their associated radio emission

Abstract: Aims. We study selected properties of solar energetic particle (SEP) events as inferred from their associated radio emissions. Methods. We used a catalogue of 115 SEP events, which consists of entries of proton intensity enhancements at one AU, with complete coverage over solar cycle 23 based on high-energy (∼68 MeV) protons from SOHO/ERNE. We also calculated the proton release time at the Sun using velocity dispersion analysis (VDA). After an initial rejection of cases with unrealistic VDA path lengths, we as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 66 publications
5
52
1
4
Order By: Relevance
“…Radio emissions have a rich diagnostic potential about the acceleration and propagation of solar energetic particles (Kouloumvakos et al 2015). Additionally, they provide important information on the location and temporal evolution of the particle release processes from the corona into the IP medium (Agueda et al 2014).…”
Section: Radio Datamentioning
confidence: 99%
“…Radio emissions have a rich diagnostic potential about the acceleration and propagation of solar energetic particles (Kouloumvakos et al 2015). Additionally, they provide important information on the location and temporal evolution of the particle release processes from the corona into the IP medium (Agueda et al 2014).…”
Section: Radio Datamentioning
confidence: 99%
“…Solar Type III bursts are produced by electron beams moving at speeds of order 10% of the speed of light, with radio frequency decreasing exponentially on a timescale of seconds; when these bursts occur at low frequencies, they indicate that energetic electrons (and likely protons as well) are escaping the solar corona on open magnetic field lines. Both of these classes of bursts are correlated with solar space weather events that impact Earth: coronal mass ejections and solar energetic particle (SEP) events (Kouloumvakos et al 2015). Analogous events, tracing bulk motion of plasma, may be detectable from nearby stars; and based on Sun-as-a-star data, such stellar radio bursts can be used to recover approximate dynamical properties of CMEs (Crosley et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although both SEP solar particle release (SPR) times and EM onsets have been discussed at length in the past, comparison between electron release times and proton release times has been discussed only in a few papers [e.g., Cliver et al , ; Haggerty and Roelof , ; Kouloumvakos et al , ; Kahler et al , ; Posner , ]. In Posner []'s study, the author adopted the prevailing assumption of simultaneous release of electrons and protons, but he also pointed out that “release of protons before electrons (and vice versa) is possible (E. Roelof and D. Haggerty, personal communication, 2006)”.…”
Section: Introductionmentioning
confidence: 99%
“…They found that half of GLE events the relativistic proton injection preceded that of electrons; however, the low‐intensity GLEs tend to have a later time for the proton injection. Recently, Kouloumvakos et al [] compared the proton and electron release as inferred from velocity dispersion analysis (VDA) based on Wind/3DP and Energetic and Relativistic Nuclei and Electron instrument (ERNE) data and found a 7 min average delay of near‐relativistic electrons with respect to deka‐MeV protons. Haggerty and Roelof [] studied 19 electron beam events using Electron, Proton, and Alpha Monitor (EPAM) 38–315 keV data and found that for 11 of the 19 events the arrival of 50–100 MeV protons followed by electrons within ∼3 min.…”
Section: Introductionmentioning
confidence: 99%